Antioxidant potential and anticancer activity of young ginger (Zingiber officinale Roscoe) grown under different CO2 concentration. - Ghasemzadeh, Ali; Jaafar , Hawa Z. E. (2011)
In the present study, leaves and rhizomes extract from two Malaysian young ginger (Zingiber officinale Roscoe) varieties namely: Halia Bentong and Halia Bara grown under ambient (400µ mol/mol) andelevated (800µ mol/mol) CO2 concentrations were studied for their antioxidant and in vitro anticanceractivities against two human cancer cell lines (MCF–7 and MDA–MB–231). Antioxidant activities in bothvarieties determined using thiobarbituric acid (TBA) assays increased significantly with increasing CO2 concentration from 400 to 800µ mol/mol. High antioxidant activity was observed in the rhizomes of HaliaBara grown under elevated CO2 concentration. The results showed that CO 2 enriched Halia Baraexhibited the highest anticancer activity on MCF–7 cancer cells with IC 50 values of 25.3 and 27.31 µg/mlrespectively for rhizomes and leaves extract. IC 50 values for MDA–MB–231 exhibition were 30 and 32.81µg/ml, respectively for rhizomes extract of Halia Bara and Halia Bentong. Results showed that HaliaBentong and Halia Bara possessed anticancer and antiradical properties especially when grown underelevated CO2 concentration. Antioxidant activities of ginger leaves and rhizomes could be increased orimproved by using CO2 enrichment in a controlled environment condition. Results also implied thatthese ginger varieties could be employed in ethno-medicine for the management of cancerousdiseases.